(untitled) (Fiep Bulletin - online, 2015)
Modality created by a biker named Johnny Goldberg who by some factors such as the weather couldn’t make their workouts on the street created a bicycle park that after a certain period of time became world-famous in academies around the world. However no standardization or substantiation of the modality. Through our research the prevailing method containing a physiologically based structuring is the model of periodization of Dantas (1998) quoted by SOUSA et al (2010), and we believe this may be planning which provides a period for adaptation of the practitioner mode, and thus decrease the rejection mode and also helping the practitioner to reach their goals. Rienda et al. (2012) found in his research that the most common injuries are in the lower back and knees and legs, which can be explained by the fact the posture to be based on the bike saddle to be erroneous, which can promote an excessive load on the lumbar region and of this activity requires greater movement in the knee joint during pedaling and as completion of your research it was found that most of the injuries are from a bad fit of the saddle (seat) of the bike. In conclusion our review we propose to be used the periodization proposed by SOUSA et al (2010), because it was proven through his research its satisfactory results in health-promoting environments and can also be proposed that the physical education professionals have greater attention in relation to the adjustment of the saddle, as was done through research of Rienda et al. (2012).